Pengaruh Self Efficacy Terhadap Job Crafting Dengan Person Jobfit Sebagai Variabel Moderator Pada Pegawai Dinas Pangan Kabupaten Sukoharjo - Hendrianto Hendrianto; Ahmad Husin; Retnoning Ambarwati (JURNAL WIRANOMIKA, 2024)
The problem formulation in this research is whether there is an influence of Self Efficacy on Person Jobfit for Sukoharjo Regency Food Service Office Employees? Is there an influence of Self Efficacy on Job Crafting for Sukoharjo Regency Food Service Office Employees? Is there an influence of Person Jobfit on Job Crafting for Employees? Sukoharjo Regency Food Service Office?, is there an influence of Person Jobfit on Job Crafting of Sukoharjo Regency Food Service Office Employees through Person Jobfit?. The aim of this research is to determine whether there is an influence of self-efficacy on job crafting with job person as a moderator variable. The hypothesis is that it is thought that there is an influence of self-efficacy on job crafting with job person as a moderator variable. This type of research is quantitative research. This research was carried out at the Sukoharjo district food service office by taking a sample of 29 employees. Based on the research results, the results showed that the influence of Self Efficacy on the Personal Jobfit of Sukoharjo Regency Food Service Employees was proven to be true. This is because the t-value obtained was 16.793 > ) of 0.000 (significant), because it was more than 0.05. Because the t-count value is 16.793r1.703 with a significance level ( > t-table 1.703, there is no influence of Self Efficacy on the Personal Jobfit of Sukoharjo Regency Food Service Employees. The second statement states that the influence of Self Efficacy on Job Crafting of Sukoharjo Regency Food Service Employees is proven to be true. This is because the t-value obtained is 3.775 > ) of 0.000 (significant), because it is more or less than 0.05. Because the t-count value is 3.775r1.703 with a significance level ( > t-table 1.703, there is an influence of Self Efficacy on Job Crafting of Sukoharjo Regency Food Service Employees. The third statement which states that there is an influence of Personal Job Fit on Job Crafting of Sukoharjo Regency Food Service Employees is not proven to be true. This is because the t-value obtained is 1.890 > ) of 0.059 (significant), because it is more than 0.05. Because the t-count value is 0.068r1.703 with a significance level ( < t-table 1.703, there is no influence of Personal Jobfit on Job Crafting of Sukoharjo Regency Food Service Employees. It has been proven that the influence of Self Efficacy on Job Crafting with Personal Jobfit as a mediating variable among Food Service Employees in Sukoharjo Regency is true. This is because the t-count value was 1.804 > 1.703. Because the t-count value is 1.804 > t-table 1.703, then Personal Jobfit as a mediating variable is not suitable to use. Self Efficacy with Job CraftingKeywords: Self Efficacy, Job Crafting, Person JobfitÂ